2004
DOI: 10.1111/j.1080-8620.2004.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Depreciation of Residential Real Estate: Microlevel Space and Time Analysis

Abstract: Three elements in the study of real estate depreciation that warrant further consideration are uncovered: the spatial variation of depreciation on a micro scale, the variability of depreciation within a single market across time and the recognition of land value as an influence in modeling real property prices. Taken together, these three dimensions provide an opportunity to further expand the understanding of residential economic depreciation while enhancing the predictive power of real estate market models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 21 publications
0
51
1
1
Order By: Relevance
“…It is expected that property age has a positive impact on income capitalization rate. The empirical results by Geltner and Fisher (2007); Smith (2004); Malpezzi et al (1987) and Cannaday and Sunderman (1986) show depreciation may present nonlinear change with an increase in property age. The age of a property and its income capitalization rate may have a nonlinear relationship, and thus the age square of property is added.…”
Section: Level 1 Variablesmentioning
confidence: 95%
“…It is expected that property age has a positive impact on income capitalization rate. The empirical results by Geltner and Fisher (2007); Smith (2004); Malpezzi et al (1987) and Cannaday and Sunderman (1986) show depreciation may present nonlinear change with an increase in property age. The age of a property and its income capitalization rate may have a nonlinear relationship, and thus the age square of property is added.…”
Section: Level 1 Variablesmentioning
confidence: 95%
“…They suggested that there are three major factors that contribute to residential consumer purchasing decision: Lifestyle, Prestige, and Security. After their research, number of studies in residential consumer preference has increased with wider perspective, including the research by Daly (2003) discussing the importance of consumer perception in valuation of residential products; pricing of residential product versus the building age (Smith, 2004); planned versus non-planned community development (Eves, 2006); study about residential consumer heterogeneity behavior by Hoshino (2008); and study made by Davison et al (2009) who discussed about the property developer brand and price which affects the consumer preference, From the following research above we can see that there are several factor that affecting consumer preference when they decided to purchase a property product. Factors such as design, planned development and prestige play significant part in price setting in Indonesia.…”
Section: Previous and Related Studies On Consumer Preferences In Realmentioning
confidence: 99%
“…There is a large stream of literature investigating the depreciation (and renewal) of urban areas (e.g. Brueckner & Rosenthal, 2009;Coulson & Bond, 1990;Harding et al, 2007;Rosenthal, 2008;Smith, 2004). Abandoned industrial sites are often large and may well have a negative impact on the neighborhoods in which they are located and become a disamenity for the nearby residential areas.…”
Section: Theoretical Backgroundmentioning
confidence: 99%